Forecasting oil tanker shipping market in crisis periods: Exponential smoothing model application - George Moiseev (Asian Journal of Shipping and Logistics (AJSL), 2021)
This paper fills the gap in the literature of applying an exponential smoothing model in the oil shipping market forecasting. The author refines the adaptive combined model with B-criterion based on Brown's model with modification by Trigg and Leach. Forecasting the values of the average time-charter equivalent of a tanker along 6 different routes of oil transportation in the world ocean during the crisis period 2015-2019. The accuracy of the proposed method is superior to naive, autoregression methods and machine learning models in all used error metrics. The obtained accuracy in 71% of cases is available for commercial use by operators and charterers of the tanker fleet.
Keywords: 650; Oil; Tanker; Time-charter; Forecasting; Exponential smoothing; Adaptive combined model; Brown; Trigg; Leach